The influence of training intensity, airway infections and environmental conditions on seasonal variations in bronchial responsiveness in cross-country skiers - Heir, T.; Larsen, S. (Scandinavian Journal of Medicine & Science in Sports, 1995)
The influence of physical training, airway infections and environmental conditions on changes in bronchial responsiveness to methacholine during a training and competitive season was studied in 19 high-performance male cross-country skiers 19-21 years old. The longitudinal changes in the methacholine concentration required for a 10% fall in FEV1 (PC10) were negatively correlated with the changes in the volume of physical activity at an intensity level above 90% of maximal heart rate. The variation in physical activity at this intensity level accounted for 54.8% of the change in PC10. No association was found, however, with regard to physical activity at lower intensity levels. Seasonal variation in PC10 was not associated with the changes in occurrence or duration of airway infections provided that the PC10 measurement was postponed for 3-6 weeks after the onset of a recent infection. Seasonal variation in PC10 seemed not to be associated with variations in ambient levels of air pollutants or aeroallergens. PC10 was lowest at the end of the coldest part of the year. In conclusion, seasonal variation in bronchial responsiveness in high-performance cross-country skiers could to a great extent be explained by changes in the volume of physical activity at a very high intensity level.